ChemInform Abstract: Solid‐State Protein‐Carbohydrate Interactions and Their Application in the Food Industry. Issue 22 (15th May 2015) - Soltanizadeh, Nafiseh; Mirmoghtadaie, Leila; Nejati, Fatemeh; Najafabadi, Leila Izadi; Heshmati, Maryam Khakbaz; Jafari, Maryam
Abstract: Review: 99 refs.